Shaped phase change material and preparation method thereof
By using a low eutectic mixed salt system and the combination of reinforcement materials and porous adsorption materials, the existing medium and low temperature phase change materials have been solved, and the standardized phase change materials with excellent performance and low cost are achieved, which are suitable for pharmaceutical cold chain logistics and other industries.
Patent Information
- Application Number
- CN202411340600.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing medium and low temperature phase change materials have problems such as large supercooling, phase separation, and easy leakage. The preparation process is complex and the cost is high, making it difficult to meet the needs of industries such as pharmaceutical cold chain logistics.
A low eutectic mixed salt system is adopted, including disodium hydrogen phosphate dodecanohydrate, sodium carbonate decahydrate and sodium sulfate decahydrate, combined with reinforcement materials and porous adsorption materials, and a shaped phase change material is formed through a simple preparation method, avoiding problems such as supercooling and phase separation.
It has achieved the effect of suitable phase transition temperature, high latent heat of phase transition, no liquid leakage, non-toxic and non-flammable, small supercooling, and phase-free separation. It has a simple preparation process and low cost. It is suitable for storing drugs at room temperature of 20-30℃.
Smart Images

Figure CN119552636A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to a shaped phase change material and a preparation method thereof. Background Art
[0002] Phase change energy storage technology has great research and application value in the fields of wind power energy saving, industrial waste heat, battery thermal management, cold chain logistics, etc. due to its unique physical and chemical properties. Among them, medium and low temperature phase change thermal storage materials with a phase change temperature of 5 to 40°C can be widely used in solar building heating, building energy saving, electronic equipment thermal management and other industries. With the continuous development of the current pharmaceutical cold chain logistics industry, the industry has conducted more and more research on low-temperature phase change materials, but there are relatively few related studies on medium and low temperature phase change materials.
[0003] Some cold chain logistics companies have developed some medium and low temperature phase change materials for suitable temperature ranges. Usually, organic materials such as fatty acids are preferred. Most of these materials are low-cost and have low supercooling. They can be compounded with materials such as polyols and aliphatic hydrocarbons to obtain phase change materials for the required temperature range, but the disadvantages are large volume changes and flammability. At the same time, some companies have begun to develop phase change materials with hydrated inorganic salts as the main components, but there are still some problems. For example, CN 114958309 A discloses a phase change material with a phase change temperature of 18 to 20 ° C and a preparation method thereof. Inorganic salts are used as the main material, thickeners, nucleating agents, and crystal modifiers are used as auxiliary materials to improve the performance of phase change materials, and thickeners must be added to prevent phase separation, and nucleating agents and crystal modifiers are added to suppress supercooling. The problem of chloride salts corroding metal containers and leaking cannot be avoided. In addition, during the logistics transportation process, the volume expansion of the phase change easily causes the packaging container to burst, greatly affecting the insulation effect and the quality of the goods, and polluting the environment. In academic research, there is a preparation method of phase change microcapsules, such as the public literature (Liu Yuan. Preparation and performance research of organic / inorganic shaped composite phase change materials [D]. Nanchang University, 2019.). This shaping preparation process is relatively complicated, and the chemical raw materials of wall materials / shell materials are expensive, which is not suitable for large-scale industrial production.
[0004] Therefore, there is an urgent need to develop a shaped phase change material and a preparation method thereof with excellent performance, low cost and simple preparation process. Summary of the invention
[0005] In view of this, the present invention proposes a shaped phase change material and a preparation method thereof. The prepared phase change material has a suitable phase change temperature, a high phase change latent heat, no phase separation, no liquid leakage, is non-toxic and non-flammable, non-corrosive, and has a small degree of supercooling. At the same time, the preparation process is simple, the source of raw materials is abundant and the cost is low, and it can be widely used for storing medicines at room temperature with a storage and transportation temperature of 20 to 30°C, so as to solve the problems of large degree of supercooling, phase separation, and easy leakage of traditional medium and low temperature phase change materials.
[0006] On the one hand, the present invention provides a shaped phase change material, which comprises the following constituent raw materials by mass percentage: 45.8-56.7% disodium hydrogen phosphate dodecahydrate, 7.9-22.9% sodium carbonate decahydrate, 15-30% sodium sulfate decahydrate, 2.46-4.05% reinforcing material, and 15-20% adsorption material.
[0007] First, in the present invention, although sodium carbonate decahydrate can assist in adjusting the phase change temperature and provide the thermal response speed of the phase change material, a single sodium carbonate decahydrate is easy to react with carbon dioxide in the air to form sodium carbonate, which may cause the chemical composition of the material to change and affect its long-term stability; although sodium sulfate decahydrate can further reduce the phase change temperature and is not easily affected by environmental factors, its thermal conductivity is poor, and when used alone, it may not provide sufficient flexibility to adjust the comprehensive performance of the PCM, especially when the phase change temperature or other physical properties need to be fine-tuned. The disodium hydrogen phosphate dodecahydrate used in the present invention provides a basic phase change temperature range for the phase change material, which can initially meet the requirements of maintaining medium and low temperatures for logistics and transportation. The combined sodium carbonate decahydrate and sodium sulfate decahydrate work together to further fine-tune the phase change temperature, so that the final phase change material can further work within the required temperature range. In addition, the mixed use of multiple hydrated inorganic salt materials may further enhance the stability of the entire phase change material system. At the same time, sodium carbonate decahydrate and sodium sulfate decahydrate have a higher thermal conductivity, which helps to further improve the thermal conductivity of the phase change material (PCM), thereby accelerating the thermal response speed.
[0008] Secondly, the reinforcing material used in the present invention can be tightly combined with the molten inorganic salt material formed in the preparation process and evenly dispersed in the pores of the adsorption material, which can optimize the impregnation shaping effect and improve the overall performance of the shaped phase change material.
[0009] By adopting the above technical scheme, the low eutectic mixed salt prepared by the present invention, i.e., a mixture of disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate and sodium sulfate decahydrate, has a small degree of supercooling under low temperature conditions, a stable solidification phase change platform, and the formed phase change material has an obvious eutectic point. Compared with the use of a single hydrated inorganic salt in the prior art, it can effectively avoid supercooling, phase separation and other phenomena that are very easy to occur during the phase change process; in addition, there is no need to add a high-viscosity thickener or find a nucleating agent and a crystal modifier that matches the crystal form.
[0010] Furthermore, the reinforcing material is an active substance or a crystal; the active substance is selected from one of nano calcium carbonate, nano alumina, nano titanium dioxide, nano montmorillonite or nano kaolin; the crystal is selected from sodium metasilicate nonahydrate or borax.
[0011] Based on the above technical solution, preferably, the particle size of the active substance is not less than 2000 mesh.
[0012] By adopting the above technical solution, the reinforcing material of the present invention has high thermal conductivity and large specific surface area, which is conducive to further enhancing the thermal conductivity of the phase change material, accelerating the absorption and release of thermal energy, and thus improving the thermal response rate. At the same time, the above reinforcing material can be used as a heterogeneous nucleation point and as a structural support, which not only helps to reduce supercooling, but also helps to maintain the uniform distribution of each component and reduce the possibility of phase separation.
[0013] Furthermore, the adsorption material is a porous adsorption material, and the porous adsorption material is selected from fumed silica (also known as "fumed white carbon black") or expanded graphite.
[0014] On the basis of the above technical solution, preferably, the specific surface area of the fumed silica is 200 to 220 m 2 / g, and a particle size of 6 to 8 μm; the particle size of the expanded graphite is 100 to 1000 meshes.
[0015] By adopting the above technical solution, both fumed silica and expanded graphite powder can be used as nucleation centers and structural supports, which not only helps to reduce the degree of supercooling and make the phase change process more controllable, but also prevents the leakage of liquid phase change materials at high temperatures and improves the thermal stability of the phase change materials.
[0016] In another aspect, the present invention provides a method for preparing the above-mentioned fixed phase change material, the method comprising the following steps:
[0017] Step 1: weigh a certain amount of disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, sodium sulfate decahydrate, reinforcing material and adsorption material according to the mass percentage for later use;
[0018] Step 2: Mix the disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate and sodium sulfate decahydrate weighed in step 1 in a certain mass ratio, stir, add the reinforcing material, continue stirring, and prepare an inorganic salt mixture;
[0019] Step 3, heating the mixture of step 2 to obtain a molten inorganic salt mixture;
[0020] Step 4: adding a portion of the molten inorganic salt of step 3 to the adsorption material, stirring, and then adding the remaining molten inorganic salt of step 3, stirring to obtain a mixed material, and sealing;
[0021] Step 5: Dry the sealed mixture in step 4 at a constant temperature for a period of time, stir it, repeat for several times, and then cool it to obtain a fixed phase change material.
[0022] By adopting the above technical solution, firstly, it can be ensured that the chemical composition in the final product is uniform, thereby ensuring the consistency and reliability of the phase change material.
[0023] Secondly, the addition of reinforcing materials helps to improve the physical properties of phase change materials, such as improving thermal conductivity, mechanical strength, etc., making phase change materials more durable and efficient in practical applications; the use of adsorbent materials (such as fumed silica or expanded graphite powder) can effectively adsorb liquid PCM (phase change material), prevent leakage, and improve product safety and stability. In addition, first combining the reinforcing material with the molten hydrated inorganic salt (particle hydrophilicity) and then mixing it with the adsorbent material can assist the adsorbent material to better encapsulate the inorganic salt. Conversely, if the adsorbent material is added first, part of the molten hydrated inorganic salt will be combined with the adsorbent material first, so that it cannot provide sufficient water phase for the reinforcing material to combine with the particles, thereby affecting the final performance of the phase change material. At the same time, adding the molten inorganic salt to the adsorbent material twice can ensure that the adsorbent material fully contacts and evenly wraps the inorganic salt, which is conducive to the formation of a stable composite material.
[0024] Finally, sealing and heating and cooling under constant temperature conditions help to form a uniform and stable phase change material, avoiding the uneven internal structure of the phase change material caused by temperature fluctuations, thereby ensuring the phase change characteristics and long-term stability of the material.
[0025] Furthermore, in step 1, the adsorption material is dried at a temperature of 80° C. for a drying time of 1.5 to 2 hours.
[0026] By adopting the above technical solution, drying the adsorption material can fully ensure that the adsorption material will not be affected by moisture, thereby avoiding the final adsorption effect being affected by moisture in the adsorption material.
[0027] Furthermore, in step 2, the stirring speed is 500-600 rpm, and the time is 30-60 min; the continued stirring speed is 700-800 rpm, and the time is 10-20 min.
[0028] Furthermore, in step three, the heating temperature is 65-75° C. and the heating time is 30-45 min.
[0029] Based on the above technical solution, preferably, the mixture in step 2 is heated in a water bath.
[0030] Further, in step 4, the After adding the volume of the molten inorganic salt in step three to the adsorbent material, it is necessary to stir at a uniform speed for 3 minutes; after adding the remaining molten inorganic salt in step three, it is necessary to stir for 5 to 7 minutes.
[0031] By adopting the above technical solution, the molten inorganic salt of the present invention can be well impregnated into the adsorbent material by dripping and mixing in batches, which not only improves the adsorption efficiency and adsorption capacity, but also helps to form a better chemical bond or physical adsorption effect, making the bond between the inorganic salt and the adsorbent material stronger, reducing the shedding or loss of the inorganic salt during use. The amount of dripping in batches of the present invention is not subject to any restriction or limitation. The present invention recommends that the first dripping amount of the molten inorganic salt be % of the total volume.
[0032] Furthermore, in step 4, the sealing method specifically includes: placing the mixed material in a container, and sealing the container opening with a single layer of plastic wrap and a high temperature resistant rubber band.
[0033] By adopting the above technical solution, it is possible to avoid complete loss of water in the mixture, thus providing a good drying environment for subsequent steps.
[0034] Furthermore, in step five, the mixture is stirred every 60 minutes, and each stirring lasts for 3 minutes; the heating temperature is 80°C, and the heating time is 6 hours; and the cooling temperature is 20-40°C.
[0035] The shaped phase change material provided by the present invention has the following beneficial effects compared with the prior art:
[0036] (1) The use of a single hydrated inorganic salt in the prior art is very likely to cause supercooling, phase separation and other phenomena during the phase change process. The present invention effectively avoids the occurrence of these problems by adopting a low eutectic mixed salt as the basic material. The present invention prepares a formula for a fixed phase change material by using a low eutectic mixed inorganic salt, without adding a high viscosity thickener, finding a crystal-matching nucleating agent and a crystal modifier, so that the fixed phase change material can reach a smaller degree of supercooling and a stable solidification phase change platform under low temperature conditions, that is, the formed fixed phase change material has a clear eutectic point. In addition, compared with low eutectic composite salt phase change materials whose phase change process is unstable due to improper ratio or lack of eutectic point, the material provided by the present invention exhibits excellent stability.
[0037] (2) The formula of the shaped phase change material prepared by the present invention has abundant raw material sources and low cost. The present invention achieves a significant improvement in the overall performance of the shaped phase change material by introducing reinforcing materials and porous adsorption materials into the formula. The addition of reinforcing materials can not only form a good combination with inorganic salts in a molten state, but also be evenly distributed in the internal structure of the porous adsorption material. The combined use of these two raw materials not only synergistically enhances the overall performance of the material, but also ensures the stability during the phase change process, thereby achieving a long-term constant temperature effect, so that the shaped phase change material of the present invention has a better impregnation shaping effect.
[0038] (3) The shaped phase change material prepared by the present invention has a suitable phase change temperature, a high latent heat of phase change, no liquid leakage, is non-toxic and non-flammable, has a small degree of supercooling, and has no phase separation. At the same time, for applications that require transportation and storage between 20 and 30°C, the shaped phase change material of the present invention can be used as an effective room temperature refrigerant to resist low temperature environments, ensure the accuracy and continuity of temperature control, and protect specific chemicals and pharmaceuticals from temperature fluctuations.
[0039] (4) The method for preparing the shaped phase change material of the present invention is simple and easy to implement, and will not cause the common electrochemical corrosion problems of inorganic phase change materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 The step cooling curves of the shaped phase change materials prepared in Examples 1 to 3 of the present invention are shown in FIG. 1 ; in the figure, a is the step cooling curve of the shaped phase change material of Example 1, b is the step cooling curve of the shaped phase change material of Example 2, and c is the step cooling curve of the shaped phase change material of Example 3;
[0042] Figure 2 The step cooling curves of the phase change materials obtained in Comparative Examples 1 to 3 of the present invention are shown in FIG. 1 ; in the figure, B1 is the step cooling curve of the phase change material of Comparative Example 1, B2 is the step cooling curve of the phase change material of Comparative Example 2, and B3 is the step cooling curve of the phase change material of Comparative Example 3;
[0043] Figure 3 The figures are physical pictures of the phase change materials prepared in Example 2 of the present invention and Comparative Examples 1-2; in the figures, W0 is a physical picture of the shaped phase change material of Example 2 after being heated in an oven, W1 is a physical picture of the shaped phase change material of Comparative Example 1 after being heated in an oven, and W2 is a physical picture of the non-shaped phase change material of Comparative Example 2 after being cyclically static;
[0044] Figure 4 The DSC curve of the shaped phase change material obtained in Example 3;
[0045] Figure 5 This is the DSC curve of the shaped phase change material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.
[0048] Table 1 Material source description
[0049]
[0050] The following are examples of the present invention.
[0051] Example 1
[0052] 1) Weigh 140g of disodium hydrogen phosphate dodecahydrate, 20g of sodium carbonate decahydrate, 40g of sodium sulfate decahydrate, 6.2g of nano calcium carbonate, and 45.8g of expanded graphite for later use;
[0053] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate in a clean container, stir at 500 rpm for 30 min until no obvious solid particles are present, then add nano calcium carbonate, stir at 700 rpm for 15 min to mix evenly, and prepare an inorganic salt mixture;
[0054] 3) placing the container containing the inorganic salt mixture in a water bath, setting the temperature to 70° C., and heating at the constant temperature for 30 min to obtain a molten inorganic salt mixture;
[0055] 4) Drying the expanded graphite at 80°C for 2h;
[0056] 5) After dropping 1 / 3 volume of the molten inorganic salt mixture into the container containing expanded graphite, stir at a constant speed for 3 minutes, then add the remaining molten inorganic salt mixture and stir thoroughly for 5 to 7 minutes;
[0057] 6) Seal the container mouth of step 5 with a single layer of plastic wrap and a high temperature resistant rubber band, dry at 80°C for 1 hour and stir for 3 minutes, repeat the drying-stirring process 6 times, and cool at room temperature (36°C) to obtain a fixed phase change material.
[0058] The phase change solidification platform temperature of the fixed phase change material formed in this embodiment is 25.3°C, and the supercooling degree is <0.1°C.
[0059] Example 2
[0060] 1) Weigh 140g of disodium hydrogen phosphate dodecahydrate, 40g of sodium carbonate decahydrate, 20g of sodium sulfate decahydrate, 10g of nano-alumina, and 37g of fumed white carbon black for later use;
[0061] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate, stir at 500 rpm for 60 min until no obvious solid particles are present, then add nano-alumina, stir at 700 rpm for 20 min to mix evenly, and prepare an inorganic salt mixture;
[0062] 3) placing the container containing the inorganic salt mixture in a water bath, setting the temperature to 75° C., and heating at the constant temperature for 45 minutes to obtain a molten inorganic salt mixture;
[0063] 4) Drying the fumed silica at 80°C for 2h;
[0064] 5) After dropping 2 / 3 volume of the molten inorganic salt mixture into the container containing fumed silica, stir at a constant speed for 3 minutes, then add the remaining molten inorganic salt mixture and stir thoroughly for 5 to 7 minutes;
[0065] 6) Seal the container mouth with a single layer of plastic wrap and a high temperature resistant rubber band, dry at 80°C for 1 hour, then stir for 3 minutes, repeat the drying-stirring process 6 times, and cool at room temperature (39°C) to obtain a fixed phase change material.
[0066] The phase change solidification platform temperature of the fixed phase change material formed in this embodiment is 27.4°C, and the supercooling degree is 0.1°C.
[0067] Example 3
[0068] 1) Weigh 120g of disodium hydrogen phosphate dodecahydrate, 60g of sodium carbonate decahydrate, 20g of sodium sulfate decahydrate, 10g of nano titanium dioxide, and 52g of fumed white carbon black for later use;
[0069] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate, stir at 600 rpm for 40 min until no obvious solid particles are present, then add nano titanium dioxide, stir at 800 rpm for 20 min to mix evenly, and prepare an inorganic salt mixture;
[0070] 3) placing the container containing the inorganic salt mixture in a water bath, setting the temperature to 70° C., and heating at the constant temperature for 40 minutes to obtain a molten inorganic salt mixture;
[0071] 4) Drying the fumed silica at 80°C for 2h;
[0072] 5) After dropping 1 / 2 volume of the molten inorganic salt mixture into the container containing fumed silica, stir at a constant speed for 3 minutes, then add the remaining molten inorganic salt mixture and stir thoroughly for 5 to 7 minutes;
[0073] 6) Seal the container mouth with a single layer of plastic wrap and a high temperature resistant rubber band, dry at 80°C for 1 hour, then stir for 3 minutes, repeat the drying-stirring process 6 times, and cool at room temperature (34°C) to obtain a fixed phase change material.
[0074] The phase change solidification platform temperature of the fixed phase change material formed in this embodiment is 24.7°C, and the supercooling degree is 0.5°C.
[0075] The following are comparative examples of the present invention.
[0076] Comparative Example 1
[0077] The difference from Example 2 is that no reinforcing material-nano alumina is added. The preparation of this comparative example specifically includes the following steps:
[0078] 1) Weigh 140 g of disodium hydrogen phosphate dodecahydrate, 40 g of sodium carbonate decahydrate, 20 g of sodium sulfate decahydrate, and 37 g of fumed silica for later use;
[0079] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate, and stir at 500 rpm for 60 min until there are no obvious solid particles and the mixture is uniform;
[0080] 3) placing the container containing the inorganic salt mixture in a water bath, setting the temperature to 75° C., and heating at the constant temperature for 45 minutes to obtain a molten inorganic salt mixture;
[0081] 4) Drying the fumed silica at 80°C for 2h;
[0082] 5) After dropping 2 / 3 volume of the molten inorganic salt mixture into the container containing fumed silica, stir at a constant speed for 3 minutes, then add the remaining molten inorganic salt mixture and stir thoroughly for 5 to 7 minutes;
[0083] 6) Seal the container mouth with a single layer of plastic wrap and a high temperature resistant rubber band, dry at 80°C for 1 hour, then stir for 3 minutes, repeat the drying-stirring process 6 times, and cool at room temperature (39°C) to obtain a fixed phase change material.
[0084] The phase change solidification platform temperature of the phase change material formed in this comparative example is 26.1°C, and the supercooling degree is 0.9°C.
[0085] Comparative Example 2
[0086] The difference from Example 3 is that 10 g of sodium carboxymethyl cellulose is used to replace 52 g of fumed silica. The preparation of this comparative example specifically includes the following steps:
[0087] 1) Weigh 120g of disodium hydrogen phosphate dodecahydrate, 60g of sodium carbonate decahydrate, 20g of sodium sulfate decahydrate, 10g of nano titanium dioxide, and 10g of sodium carboxymethyl cellulose for later use;
[0088] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate, stir at 600 rpm for 40 min until no obvious solid particles are present, then add nano titanium dioxide and sodium carboxymethyl cellulose, and stir at 800 rpm for 20 min to mix evenly;
[0089] 3) Place the mixture container in a water bath and set the temperature to 70° C., heat at a constant temperature for 40 minutes, and then cool at room temperature (34° C.) to obtain an amorphous phase change material.
[0090] The phase change solidification platform temperature of the amorphous phase change material formed in this comparative example is 24.0°C, and the supercooling degree is 3.7°C.
[0091] Comparative Example 3
[0092] The difference from Example 3 is that the molten inorganic salt mixture in step 3 is dripped into the fumed silica at one time. Specifically comprising:
[0093] 1) Weigh 120g of disodium hydrogen phosphate dodecahydrate, 60g of sodium carbonate decahydrate, 20g of sodium sulfate decahydrate, 10g of nano titanium dioxide, and 52g of fumed white carbon black for later use;
[0094] 2) Mix disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, and sodium sulfate decahydrate, stir at 600 rpm for 40 min until no obvious solid particles are present, then add nano titanium dioxide, stir at 800 rpm for 20 min to mix evenly, and prepare an inorganic salt mixture;
[0095] 3) placing the container containing the inorganic salt mixture in a water bath, setting the temperature to 70° C., and heating at the constant temperature for 40 minutes to obtain a molten inorganic salt mixture;
[0096] 4) Drying the fumed silica at 80°C for 2h;
[0097] 5) Add the molten inorganic salt mixture all at once into the container containing fumed silica, and stir at a constant speed for 5 to 7 minutes;
[0098] 6) Seal the container mouth with a single layer of plastic wrap and a high temperature resistant rubber band, dry at 80°C for 1 hour, then stir for 3 minutes, repeat the drying-stirring process 6 times, and cool at room temperature (34°C) to obtain a fixed phase change material.
[0099] The phase change solidification platform temperature of the shaped phase change material formed in this comparative example is 23.6°C, and the supercooling degree is 1.2°C.
[0100] The test results of the phase change solidification platform temperature and supercooling degree of the phase change materials prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 are recorded in Table 2 below.
[0101] Table 2 Test results of embodiments and comparative examples
[0102] sample Phase change solidification platform temperature / ℃ Subcooling degree / ℃ Platform heat release time / min Example 1 25.3 <0.1 67 Example 2 27.4 0.1 74 Example 3 24.7 0.5 63 Comparative Example 1 26.1 0.9 42 Comparative Example 2 24.0 3.7 28 Comparative Example 3 23.6 1.2 61
[0103] From the test results in Table 2, it can be seen that the phase change solidification platform temperature of the shaped phase change materials prepared in Examples 1 to 3 is all within the range of 20 to 30°C, the supercooling is less than 1°C, and the platform exothermic time is >60min (the mass range of molten inorganic salts in all samples is 210±5g). The platform exothermic time of Comparative Examples 1 to 2 is reduced by at least 30% compared with that of Examples 2 to 3; the exothermic time results of Comparative Example 3 and Example 3 are similar in that the formula is the same and only the preparation steps are different, but the supercooling is poor. It can be explained that the main inorganic salts in the shaped phase change materials prepared by the present invention have eutectic points, good nucleus growth, and a stable phase change process. Therefore, it can be considered that the shaped phase change materials prepared by the present invention can be applied to thermal interface materials, battery thermal management, logistics, chemicals and other fields.
[0104] In addition, from the perspective of the platform heat release time of the phase change materials prepared in Examples 1 to 3 in Table 2, in the present invention, the greater the mass fraction of the adsorption material in the total material, the greater the degree of reduction in latent heat.
[0105] The inventors further conducted the following performance tests on the above embodiments and comparative examples, including:
[0106] (1) Step cold test
[0107] The phase change materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively placed in small ziplock bags / 250 ml glass containers, and placed in a refrigerator. The refrigerator temperature was set to 2 to 8° C. The probe of the SL-SWSSN-4G intelligent temperature and humidity communication recorder was inserted into the middle of the material, and the temperature change was recorded every 1 minute. Finally, the collected temperature data of the PCM phase change process were analyzed to obtain the following: Figure 1 , 2 The step cooling curve is shown.
[0108] (2) Stability test
[0109] Take about 10g of the phase change material powder prepared in Example 2 and Comparative Example 1, place it on filter paper, then place the filter paper in a petri dish, seal it and put it in an oven, set the temperature to 60°C, take out the petri dish after 30 minutes, and observe the thermal stability of the sample and whether there is material leakage on the filter paper. The results are as follows Figure 3 (W0, W1) as shown.
[0110] The phase change material prepared in Comparative Example 2 was tested at a low temperature of 2-8°C for 16 hours, then taken out and placed at room temperature (20-40°C) to observe the stability of the material in the container. Figure 3 (W2) as shown.
[0111] (3)DSC test
[0112] The phase change enthalpy of the phase change material is tested according to the relevant records in GB / T 19466.1 "Plastic Differential Scanning Calorimetry (DSC) Part 1: General Rules", wherein the differential scanning calorimeter used in the test should be calibrated and verified, and the cooling device supporting the measuring instrument should be able to cool to below -70°C, and the weighing instrument used should be accurate to 0.01mg. The test specifically includes: taking the shaped phase change material prepared in Example 3 and Comparative Example 3 as an example, the sampling mass for each test should be 3mg to 7mg, the test is carried out in a nitrogen atmosphere, the standard substance used is indium, and the temperature rise / fall scan rate is 5°C / min or 10°C / min. The results are as follows: Figure 4 , Figure 5 shown.
[0113] Depend on Figure 1 It can be seen that the shaped phase change material prepared by the present invention has a stable step cooling curve Tt diagram, a small supercooling degree, and a solidification exothermic time of more than 60 minutes (the mass range of the molten inorganic salt is 210±5g). In the present invention, the exothermic time decreases with the increase of the mass of the adsorbent material, and the supercooling degree increases with the increase of the mass ratio of sodium carbonate decahydrate and sodium sulfate decahydrate. The supercooling degree of the formula within the scope of the present invention is less than 1°C, the crystal growth is good, the phase change conversion rate is high, and the thermal enthalpy of the phase change material can be utilized to the maximum extent.
[0114] Depend on Figure 2 It can be seen that the reinforcing material, the adsorbent material, and the method of adding the molten inorganic salt to the adsorbent material in the preparation step all have different degrees of influence on the phase change material.
[0115] Combining the step cooling curves of Example 2 and Comparative Example 1, the phase change point of the shaped phase change material prepared without adding the reinforcing material is slightly lower, but the supercooling phenomenon is obvious, the curve is not stable enough, and the heat release time is reduced by about 42%. The reason for this phenomenon is that the reinforcing material is a functional inorganic material, and the particle surface is hydrophilic and oleophobic. The reinforcing material utilizes its binding force with the molten inorganic salt phase change material matrix to improve the overall performance of the shaped phase change material, and assists the main energy storage phase change material (molten inorganic salt) to be evenly dispersed in the adsorption material;
[0116] Combining the step cooling curves of Example 3 and Comparative Example 2, the step cooling curve of the low eutectic inorganic salt material that has not been fixed by the adsorption material has a very large degree of supercooling, the phase change process is extremely unstable, and the heat release time is reduced by about 55.5%. The reason for this phenomenon is that the molten inorganic salt phase change material is not encapsulated by the porous adsorption material, resulting in a temperature fault in the phase change process, and the supercooling delay phenomenon is serious, resulting in a strong amorphous state (glass state) in the crystallization process.
[0117] Combining the step cooling curves of Example 3 and Comparative Example 3, it can be seen that compared with the step cooling curves of adding the molten inorganic salt dropwise, the difference between the heat release time and the phase change temperature platform is not large, except that the supercooling degree of the step cooling curve is increased. Therefore, the phase change enthalpy is further analyzed by differential scanning calorimetry DSC test. See the attached Figure 4 and attached Figure 5 .
[0118] It can be seen that the reinforcing material is conducive to the uniform impregnation of the low-melting hydrated inorganic salt, thereby improving the adsorption rate of the fixed phase change material on the inorganic salt, and the porous adsorption material is conducive to the overall stability and phase change constant temperature of the fixed phase change material. The composite use of reinforcing materials and adsorption materials has a certain synergistic effect, which can make the phase change process of the fixed phase change material more stable and achieve the optimization of the packaging shaping effect, so as to be suitable for various medium and low temperature phase change application fields, such as battery thermal management, logistics, etc.
[0119] Depend on Figure 3 (W0) It can be seen that the shaped phase change material prepared in Example 2 can maintain good thermal stability under a high temperature environment for a certain period of time and is not prone to leaking liquid materials.
[0120] Depend on Figure 3 (W1) It can be seen that the fixed phase change material prepared in Comparative Example 1 has poor thermal stability and leaks some liquid material under high temperature environment for a certain period of time.
[0121] Depend on Figure 3 (W2) It can be seen that the non-stereotyped phase change material prepared in Comparative Example 2 needs to add a thickener to increase the viscosity of the liquid material to avoid the stratification phenomenon caused by the density difference of the inorganic salt, but stratification is still prone to occur after the freeze-thaw cycle.
[0122] It can be seen from this that the directional phase change material prepared by the present invention has a suitable phase change temperature, a high latent heat of phase change, no liquid leakage, is non-toxic and non-flammable, has a small degree of supercooling, and has no phase separation.
[0123] Depend on Figure 4 It can be seen that the phase change point T of the shaped phase change material prepared in Example 3 is onset It is 22.2℃, and the phase change enthalpy is 127.4J / g, which is slightly lower than the phase change temperature of the cooling curve c.
[0124] Depend on Figure 5 It can be seen that the phase change point T of the shaped phase change material prepared in Comparative Example 3 is onset The phase change enthalpy is 14.8℃ and 104.4J / g, which is lower than the phase change temperature of step cooling curve B3. In addition to the supercooling phenomenon, this is also because the mixing step 4 does not use the stepwise dropwise mixing, and the hydrated inorganic salt cannot be well impregnated into the adsorption material, thereby blocking the heat transfer.
[0125] Combined with the DSC curves of Example 3 and Comparative Example 3, it can be seen that adding molten inorganic salts to the adsorbent material in batches can maximize the adsorption of the material, utilize its phase change enthalpy, and reduce the influence of the pores of the adsorbent material on the overall heat transfer of the material, compared with adding molten inorganic salts all at once. The enthalpy value and starting temperature of DSC indicate that the prepared stereotyped phase change material has a suitable phase change temperature and a reliable high latent heat value, which can replace the traditional non-stereotyped phase change material and avoid the leakage and large supercooling caused by the solid-liquid phase change.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A shaped phase change material, characterized in that: The phase change material comprises the following raw materials by mass percentage: 45.8-56.7% disodium hydrogen phosphate dodecahydrate, 7.9-22.9% sodium carbonate decahydrate, 7.6-15.9% sodium sulfate decahydrate, 2.46-4.05% reinforcing material, and 15-20% adsorption material.
2. The shaped phase change material according to claim 1, characterized in that: The reinforcing material is an active substance or a crystalline substance; The active substance is selected from one of nano calcium carbonate, nano alumina, nano titanium dioxide, nano montmorillonite or nano kaolin; The crystals are selected from sodium metasilicate nonahydrate or borax.
3. The shaped phase change material according to claim 2, characterized in that: The particle size of the active substance is not less than 2000 mesh.
4. The shaped phase change material according to claim 1, characterized in that: The adsorption material is a porous adsorption material, and the porous adsorption material is selected from fumed silica or expanded graphite.
5. The shaped phase change material according to claim 4, characterized in that: The specific surface area of the fumed silica is 200 to 220 m 2 / g, and a particle size of 6 to 8 μm; the particle size of the expanded graphite is 100 to 1000 meshes.
6. A method for preparing the shaped phase change material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step 1: weigh a certain amount of disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate, sodium sulfate decahydrate, reinforcing material and adsorption material according to the mass percentage for later use; Step 2: Mix the disodium hydrogen phosphate dodecahydrate, sodium carbonate decahydrate and sodium sulfate decahydrate weighed in step 1, stir, add the reinforcing material, continue stirring, and prepare an inorganic salt mixture; Step 3, heating the mixture of step 2 to obtain a molten inorganic salt mixture; Step 4: adding a portion of the molten inorganic salt of step 3 to the adsorption material, stirring, and then adding the remaining molten inorganic salt of step 3, stirring to obtain a mixed material, and sealing; Step 5: Dry the sealed mixture in step 4 at a constant temperature for a period of time, stir it, repeat for several times, and then cool it to obtain a fixed phase change material.
7. The method according to claim 6, characterized in that In step 1, the adsorption material is dried at a temperature of 80° C. for a drying time of 1.5 to 2 hours.
8. The method according to claim 6, characterized in that In step three, the heating temperature is 65-75° C. and the heating time is 30-45 min.
9. The method according to claim 6, characterized in that In step 4, a portion of the molten inorganic salt of step 3 is added to the adsorbent material, stirred, and then the remaining molten inorganic salt of step 3 is added, stirred, a mixed material is obtained, and sealed, which specifically includes: Will The molten inorganic salt obtained in step three is added to the adsorbent material by volume, stirred, and then the remaining molten inorganic salt in step three is added, stirred to obtain a mixture, and sealed.
10. The method according to claim 6, characterized in that In step 5, the constant temperature drying temperature is 80°C, and the total cumulative time is 6 hours; the mixture is stirred every 60 minutes, and each stirring time is 3 minutes; the cooling temperature is 20-40°C.
Citation Information
Patent Citations
Phase change material with phase change temperature of 18-20 DEG C and preparation method thereof
CN114958309A
Composite phase change material and preparation method thereof
CN110591653A
Heat storage material composition, heat storage system for air-conditioning of architectural structure
JP2019151762A
A phase change heat retaining material
WO2018188884A1
Heat storage material composition and heat storage system for building air conditioning
WO2019172260A1
Cited By
Nanometer microcapsule composite phase change cold storage method suitable for fruit and vegetable cold-chain logistics
CN121252552A